Role of Rhizosphere Soil Microbes in Adapting Ramie (Boehmeria nivea L.) Plants to Poor Soil Conditions through N-Fixing and P-Solubilization - Shenglan Wu (MDPI AG, 2021)
The N-fixing and P-solubilization functions of soil microbes play a vital role in plant adaptation to nutrient-deficiency conditions. However, their exact roles toward the adaptation of ramie to poor soil conditions are still not clear. To fill this research gap, the N-fixing and P-solubilization efficiencies of soils derived from the rhizosphere of several ramie genotypes with different levels of poor soil tolerance were compared. Correlations between the N-fixing, P-solubilization efficiency, and the poor soil tolerable index were analyzed to quantify their contributions towards the adaptation of ramie plants to poor soil conditions. To explore how the microorganisms affected the potential of N-fixing/P-solubilization, the activities of the nutrients related the soil enzymes were also tested and compared. The results of this study confirm the existence of N-fixing and P-solubilization bacteria in the ramie rhizosphere of the soil. The number of N-fixing bacteria varied from 3010.00 to 46,150.00 c.f.u. per gram dry soil for the ramie treatment, while it was only 110.00 c.f.u. per gram dry soil for treatment without ramie cultivation. The average P-solubilization efficiency of ramie treatment was almost five times higher than that of the control soil (0.65 vs. 0.13 mg mL−1). The significant correlations between the poor soil tolerance index and the N-fixing bacteria number (r = 0.829)/nitrogenase activity (r = 0.899) suggest the significantly positive role of N-fixing function in the adaptation of ramie plants to poor soil. This is also true for P-solubilization, as indicated by the significant positively correlation coefficients between the ramie poor soil tolerance index and P-solubilization efficiency (0.919)/acid phosphatase activity (0.846). These characteristics would accelerate the application of “holobiont” breeding for improving ramie nutrient use efficiency.